Answer

Verified

372.9k+ views

**Hint:**This problem is from arithmetic progression. We are given three terms in the form of n and they are in A.P. so it is clear that there is a common difference d in two consecutive terms. So we will form two equations in n and d form. One equation from first and second term and the other is from first and third term. On solving them we will get the value of n and d. from that we will find the numbers. So let’s solve it!

**Step by step solution:**

Given that \[\left( {2n - 1} \right)\] , \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P.

So let d be the common difference. Then we can write,

\[\left( {3n + 2} \right) - \left( {2n - 1} \right) = d\] ……..equation1

Now on solving the equation above we get,

\[ \Rightarrow 3n + 2 - 2n + 1 = d\]

Taking similar terms on one side we get,

\[ \Rightarrow 3n - 2n + 2 + 1 = d\]

\[ \Rightarrow n + 3 = d\] …….equation1.1

Now the difference in first and third term is 2d. then we can write,

\[\left( {6n - 1} \right) - \left( {2n - 1} \right) = 2d\] …….equation2

Now on solving the equation above we get,

\[ \Rightarrow 6n - 1 - 2n + 1 = 2d\]

Taking similar terms on one side we get,

\[ \Rightarrow 6n - 2n - 1 + 1 = 2d\]

\[ \Rightarrow 4n = 2d\]

So on further simplification,

\[ \Rightarrow n = \dfrac{d}{2}\]

\[d = 2n\]

This is the value of d.

From 1.1 we get \[ \Rightarrow d - n = 3\]

Putting the value of d in the equation above,

\[ \Rightarrow 2n - n = 3\]

\[ \Rightarrow n = 3\]

This is the value of n \[ \Rightarrow n = 3\] .

Now putting the value one by one in the numbers given we get the numbers also.

First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]

Second number: \[\left( {3n + 2} \right) = 3 \times 3 + 2 = 9 + 2 = 11\]

Third number: \[\left( {6n - 1} \right) = 6 \times 3 - 1 = 18 - 1 = 17\]

**Thus the numbers are \[5,11,17\].**

**Note:**

Note that the numbers are given that they are already in A.P. so they have the relation in them. We can solve the problem by finding the value of common difference also. That is just need to find the first number and rest two can be found by adding the common difference. How? See below.

\[

\Rightarrow n + 3 = d \\

\Rightarrow d - n = 3 \\

\Rightarrow d - \dfrac{d}{2} = 3 \\

\Rightarrow \dfrac{d}{2} = 3 \\

\Rightarrow d = 3 \times 2 = 6 \\

\]

Now First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]

Then second number \[5 + d = 5 + 6 = 11\]

Then third number \[11 + d = 11 + 6 = 17\]

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail